2014
DOI: 10.1044/2014_jslhr-l-13-0236
|View full text |Cite
|
Sign up to set email alerts
|

Deaf Children With Cochlear Implants Do Not Appear to Use Sentence Context to Help Recognize Spoken Words

Abstract: Purpose The authors investigated the ability of deaf children with cochlear implants (CIs) to use sentence context to facilitate the perception of spoken words. Method Deaf children with CIs (n = 24) and an age-matched group of children with normal hearing (n = 31) were presented with lexically controlled sentences and were asked to repeat each sentence in its entirety. Performance was analyzed at each of 3 word positions of each sentence (first, second, and third key word). Results Whereas the children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 46 publications
3
21
0
1
Order By: Relevance
“…Indeed, in sentence tests, children with normal hearing recognize sentences comprising lexically easy words more easily compared with those comprising lexically difficult words (Conway, Deocampo, Walk, Anaya, & Pisoni, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in sentence tests, children with normal hearing recognize sentences comprising lexically easy words more easily compared with those comprising lexically difficult words (Conway, Deocampo, Walk, Anaya, & Pisoni, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Conway et al found that ambiguous words placed late in a sentence, and hence most able to be facilitated by contextual cues, were not more likely to be intelligible in cochlear implant users (Conway et al, 2014). In Eisenberg et al, the intelligibility benefit of words placed in sentences was seen in most, but not all cochlear implant users (Eisenberg et al, 2002).…”
Section: Changes In Top-down Systems After Deafferentation In Humansmentioning
confidence: 99%
“…First, the use of contextual cues for speech perception in hearing impaired users is dependent on the degree of hearing loss; the effect is largest when the hearing loss is mild (Başkent et al, 2010). Second, domain non-specific cognitive impairment can be seen in cochlear implant users (Kral et al, 2016; Pisoni et al, 2010), and this cognitive loss correlates with the inability to use contextual cues (Conway et al, 2014). Third, the use of contextual cues depends on one’s vocabulary and experience with language, two factors which are highly variable in cochlear implant users (Connor et al, 2006).…”
Section: Changes In Top-down Systems After Deafferentation In Humansmentioning
confidence: 99%
“…Os surdos tiveram dificuldade em utilizar o contexto da frase para melhorar o reconhecimento de palavras. Os autores concluíram que as dificuldades dos surdos podem estar relacionadas à reduzida interação entre experiências linguísticas e fatores cognitivos 23 . A Figura 2 e 3 mostrou que o maior número de habilidades pragmáticas estava associado com o maior tempo de uso de próteses auditivas e maior tempo de terapia.…”
Section: Discussionunclassified